Virtues of the Flesh - Passion and Purity in Early Islamic Jurisprudence - Maghen, Ze'ev, (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
Robust sexuality, profound spirituality and elaborate legalism are, at first glance, strange bedfellows. The conventional Western wisdom has long conceived of these several modes as comprising an antagonistic trichotomy, in which each component is opposed to the others. Classical Islam, on the other hand, envisioned a unique system of cooperation between the sensual, the ethereal and the forensic. This study employs the vast and hitherto neglected literature of Islamic purity law as a looking glass through which to examine early Muslim attitudes to the romantic and erotic. Probing Qur'ān, Ḥadīth, Tafsīr and Fiqh, it opens a window on a world of unexpectedly explicit and unrestrainedly joyful sexual expression -- a world located squarely within the confines of God's sacred law and its elucidation.